Proceedings of the Sustainable Concrete Materials and Structures in Construction 2020 - Mohd Zuki, Sharifah Salwa; Mokhatar, Shahrul Niza; Shahidan, Shahiron; Wan Ibrahim, Mohd Haziman (Springer, 2020)
Seminar on Sustainable Concrete Materials and Structures in Concrete Construction 2020 was held virtually for the first time on 24 August 2020. This event was organized by the Faculty of Civil Engineering and Built Environment (FKAAB), Universiti Tun Hussein Onn Malaysia (UTHM) in collaboration with Concrete Society of Malaysia (CSM) and Civil Engineering and Built Environment Postgraduate Society, FKAAB (CiBPS). The theme of this seminar is Toward Sustainable Green Concrete. This seminar marks the first collaboration between these three organizations.